Erotic Magic, Elegy, and Iambic in Horace’s Epodes - Zara Chadha (Eugesta, 2022)
This paper explores Horace’s engagement with Latin love elegy through the motif of magic in Epodes 5 and 17. I argue that Horace’s Canidia and the elegiac puellae are constructed in tandem as part of an ongoing dialogue between Horace’s Epodes and early love elegy. Horace literalises the elegiac lovers’ metaphorical characterisation of their mistress’ beauty as magically enchanting to construct Canidia as a witch who controls her lovers with erotic magic. Through Canidia and the theme of magic in the Epodes, Horace uses elegy to define his iambic poetics and to demonstrate that love elegy is central to his development of the Roman iambic tradition.